Campylobacter Colonization, Environmental Enteric Dysfunction, Stunting, and Associated Risk Factors Among Young Children in Rural Ethiopia: A Cross-Sectional Study From the Campylobacter Genomics and Environmental Enteric Dysfunction (CAGED) Project - Chen, Dehao; McKune, Sarah L.; Singh, Nitya; Yousuf Hassen, Jemal; Gebreyes, Wondwossen; Manary, Mark J.; Bardosh, Kevin; Yang, Yang; Diaz, Nicholas; Mohammed, Abdulmuen; Terefe, Yitagele; Roba, Kedir Teji; et al. (Frontiers in Public Health, 2021)
Livestock farming provides a possible mechanism by which smallholder farmers can meet their household need for animal source foods (ASF), which may reduce the risk of stunting. However, direct/indirect contacts with domestic animals may increase colonization by Campylobacter spp., which has been associated with Environmental Enteric Dysfunction (EED) and stunting. A cross-sectional study involving 102 randomly selected children between 12 and 16 months of age was conducted in rural eastern Ethiopia to establish prevalence rates of Campylobacter colonization, EED, and stunting, and evaluate potential risk factors. Data were collected between September and December 2018. The prevalence of EED and stunting was 50% (40% - 60%) and 41% (32% - 51%), respectively. Among enrolled children, 56% had consumed some ASF in the previous 24 hours; 47% had diarrhea and 50% had fever in the past 15 days. 54%, 63%, 71% or 43% of households owned at least one chicken, cow/bull, goat, or sheep; 54 (53%) households kept chickens indoors overnight and only half of these confined the animals. Sanitation was poor, with high levels of unimproved latrines and open defecation. Most households had access to an improved source of drinking water. The prevalence of Campylobacter colonization was 50% (41% - 60%) by PCR. In addition to the thermotolerant species C. jejuni, C. coli and C. upsaliensis, non-thermotolerant species related to C. hyointestinalis and C. fetus were frequently detected by Meta-total RNA sequencing (MeTRS). Current breastfeeding and ASF consumption increased the odds of Campylobacter detection by PCR, while improved drinking water supply decreased the odds of EED. No risk factors were significantly associated with stunting. Further studies are necessary to better understand reservoirs and transmission pathways of Campylobacter spp. and their potential impact on child health.